PENGARUH KOMUNIKASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UNIT INDUK PEMBANGUNAN JARINGAN SUMATERA I - Fajar Pasaribu (CERED Indonesia Institute, 2020)
This study aims to determine and analyze the effect of communication on employee performance and analyze the effect of training on employee performance at PT. PLN (Persero) either partially or simultaneously in the Main Unit of Sumatra I Network Development. The research approach used in this study is a quantitative approach, with the associative method. Data were collected through interviews and filling out questionnaires. The population in this study were all employees at PT. PLN (Persero) Sumatran Network Development Main Unit To determine the number of research samples used probability sampling so that the sample taken is only 87 people. The analysis technique used is Product Moment correlation and multiple correlations. The results of this study prove that communication has a significant effect on employee performance, training has a significant effect on employee performance, and communication and training both have a significant effect on employee performance.